The efficacy of venlafaxine in the treatment of women with stress urinary incontinence - Erdinc, Ali; Gurates, Bilgin; Celik, Husnu; Polat, Aytac; Kumru, Selahattin; Simsek, Mehmet (Springer Heidelberg, 2009)
To examine the efficacy of venlafaxine, which is used as an antidepressant, in the treatment of stress urinary incontinence. The study was designed as a placebo-controlled, double-blind and randomized clinical study. Patients in Group 1 (n = 20) were administered 75 mg venlafaxine, those in Group 2 (n = 20) were administered placebo for 12 weeks. All the cases were evaluated in terms of weekly incontinence episode frequency (IEF), change in void interval (VI), the Incontinence Quality of Life (I-QOL) in weeks 0, 4, 8 and 12. Additionally, PGI-S was assessed at baseline and was followed by PGI-I evaluations in weeks 4, 8 and 12. Evaluations in weeks 0, 4, 8 and 12 did not show any significant difference in IEF, VI, IQOL and PGI-I values of placebo group (p > 0.05). However, in the patients who were administered venlafaxine declines in IEF and PGI-I values as well as the elevations in VI and IQOL scores showed significant changes parallel to the increasing follow-up period (p < 0.05). Nausea was observed in 40% of cases in venlafaxine group, and 15% of those in placebo group (p < 0.05). It was seen in our study that efficacy of venlafaxine started early and the clinical efficacy associated with the use of the drug continued in the following months. Venlafaxine should be considered a clinically efficient alternative drug in the treatment of SUI.
Keywords: Venlafaxine; Antidepressant; Stress urinary incontinence